VD_FINDINFO HC / 2013 / 226 vom 26. Februar 2013 - VD Tribunal cantonal (2013)
PRESTATIONSENS GÉNÉRAL, TERRASSEMENT, PRIX FERME | 374 CO, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 310 CPC (CH), 312 al. 1 CPC (CH), 317 al. 1 let. b CPC (CH)